The anger workbook for teens : activities to help you deal with anger and frustration - Lohmann, Raychelle Cassada (New Harbinger Publications, Inc., 2019)
"It's hard being a teen in today's world--and many teens struggle with anger as a result. But what if we could teach teens to interact with their anger in a positive way? Fully revised and updated based on reader feedback, this timely second edition of The Anger Workbook for Teens includes activities based in empirically supported treatments to promote psychological flexibility, giving teens the skills they need to understand and interact with their anger, rather than simply attempting to control it"--